Trade and environment in a North American Free Trade Agreement - Greenwald, Joseph (Centre for Trade Policy and Law. Carleton University OttawaCA, 1991)
Analyzes the elements of the environment/trade nexus. Summarizes the initial position of the US government regarding environment and the NAFTA. Examines the GATT provisions. Reviews the relevant provisions in the US-Canada Free Trade Agreement and the European Community. Discusses ways in which the environment could be handled in a NAFTA (including dispute settlement).